The Effect of Muscular Endurance Exercises According to Superset Theory in some Physiological Abilities and Completion of Running 800 Meters Advanced - Suhad Qasem Al-Moussawi (Journal of Global Pharma Technology, 2018)
This study aimed to identify the effect of muscular endurance in the development of some physiological abilities to achieve an 800-meter run. The researchers hypothesized that there was a positive effect of the Super Set muscular endurance exercises in advanced race runners. The researchers used the experimental approach to suitability and the nature of the research. The study sample consisted of (10) players divided equally into experimental and control groups. The experimental group used muscle training exercises in Superset to develop physiological variables such as anaerobic and aerobic abilities and the concentration of lactic acid in blood. The control group In addition to the physiological variables such as the measurement of the levels of lactic acid in the blood (before and after) the brown effort, the experiment lasted (10) weeks and (3) units The results of the study showed that there were significant differences in some variables, such as the arithmetic mean, the standard deviation, the torsion coefficient, and the t-test of the interrelated samples. Physiology and the concentration of lactic acid in blood between the experimental and control groups. The results of the study showed the existence of random differences between the two groups in the post-test of the concentration of lactic acid before the effort.Keywords: Athletics, Running 800 meters, Superset exercises, Anaerobic and aerobic abilities and lactic acid concentration.